Trickle-Down Economics: Is It Valid in Egypt? - Kamal, Abdelmonem Lotfy Mohamed (Archives of Business Research, 2018)
<span style="line-height: 115%; font-family: 'Times New Roman',serif; mso-bidi-font-size: 11.0pt; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-bidi-font-weight: bold;" lang="EN-US">Several research papers have been conducted to investigate whether the trickle-down effect is valid in countries such as India, Switzerland, Indonesia, and others. This paper tries to get an answer to the same question for Egypt. The paper found no evidence to the trickle-down economics for the Poor in Egypt. Econometric analysis assured that high economic growth rates in Egypt were accompanied with increase in poverty rates. Decline in poverty rates in Egypt, which rarely to appear, that the Egyptian society witnessed during 1990s were largely attributed to government anti-poverty measures implemented during the Economic Reform and Structural Adjustment Program (ERSAP). These measures were mitigation policies related to Economic Reform program that the Egyptian government executed starting 1991 under IMF and World Bank supervision. Finally, the paper concluded that it is better to the Egyptian government to change its dependence on trickle-down theory of economic development into bottom-up economic development approach.